Preparation and characterization of polyacrylonitrile-based carbon fibers produced by electron beam irradiation pretreatment - Shin, Hye Kyoung; Park, Mira; Kang, Phil Hyun; Choi, Heung-Soap; Park, Soo-Jin (Journal of industrial and engineering chemistry (Seoul, Korea), 2014)
This study evaluated the feasibility of polyacrylonitrile (PAN) fibers stabilized by thermal treatment after electron beam irradiation (EBI) in the production of carbon fibers. The effects of EBI and thermal treatments on the PAN precursor were verified by FT-IR, differential scanning calorimetry (DSC), X-ray diffraction (XRD), and scanning electron microscopy (SEM). FT-IR spectra confirmed that the intensities of the CBBN stretching vibration at 2244 cm 1 significantly decreased as the thermal treatment temperature increase from 200 ℃ to 250 ℃ and the holding time from 20 min to 40 min after EBI process. This decrease was caused by the cyclization of nitrile groups upon stabilization by the EBI and thermal treatments. The thermal properties were characterized by DSC, which confirmed that the EBI affected the quantity of the released heat as well as the position of exothermic equilibrium over a wide range of low temperatures. The majority of the exothermic peaks disappeared after thermal treatment. The stabilization index (SI) values for the PAN fibers that were exposed to EBI and thermal treatment after EBI were evaluated by XRD. The SI value of the PAN fibers that were treated at 250 ℃ for 40 min after EBI was 99.21%. Additionally, the tensile strength of carbon fibers that were produced from PAN attained about 2.3 GPa, the cross-section exhibited a clear and brittle morphology. KCI Citation Count: 49